2011
DOI: 10.1002/aenm.201100137
|View full text |Cite
|
Sign up to set email alerts
|

A 4% Efficient Organic Solar Cell Using a Fluorinated Fused Subphthalocyanine Dimer as an Electron Acceptor

Abstract: Planar bilayer organic solar cells with a fluorinated fused subphthalocyanine dimer (FSubPcDimer) as an acceptor and chloroboron (III) subphthalocyanine (SubPc) as a donor obtain a 60% higher Jsc compared to cells using C60 as an acceptor, resulting in a power conversion efficiency of 4%. This is obtained thanks to the important contribution to the photocurrent of the low‐bandgap FSubPcDimer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
82
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 25 publications
(27 reference statements)
1
82
0
Order By: Relevance
“…To illustrate, the best non-fullerene-based OPV cell reported up to now, consisting of a boron subphthalocyanine chloride (SubPc) donor and a fused fluorinated SubPc dimer acceptor, achieves a PCE of 4% (ref. 17), which is comparable to the best bilayer SubPc/C 60 cells reported in the literature 19 . Additionally, it has been shown that non-halogenated SubPc, mostly known as a donor material, can act as an electronaccepting material in bilayer OPV cells 20 .…”
supporting
confidence: 71%
See 1 more Smart Citation
“…To illustrate, the best non-fullerene-based OPV cell reported up to now, consisting of a boron subphthalocyanine chloride (SubPc) donor and a fused fluorinated SubPc dimer acceptor, achieves a PCE of 4% (ref. 17), which is comparable to the best bilayer SubPc/C 60 cells reported in the literature 19 . Additionally, it has been shown that non-halogenated SubPc, mostly known as a donor material, can act as an electronaccepting material in bilayer OPV cells 20 .…”
supporting
confidence: 71%
“…Alternatives to fullerenes for vacuum-deposited small-molecule organic solar cells mainly comprise perylene derivatives 4 or halogenated (sub-) phthalocyanines [16][17][18] . However, these non-fullerene acceptors rarely show improved performance over their fullerene counterparts.…”
mentioning
confidence: 99%
“…The most common alternative acceptors that have been utilized include perylene derivatives [ 2 ] as well as (halogenated) subphthalocyanines. [3][4][5] In the optimal case, an alternative acceptor allows for a more effi cient absorption of solar light compared to fullerenes, or a higher V oc through more optimal energy level alignment. This is because the V oc of organic solar cells scales with the interface gap energy I G , being the difference between the highest occupied molecular orbital (HOMO) energy of the donor and the lowest unoccupied molecular orbital (LUMO) energy of the acceptor.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, DERHD7T has a rather high molar absorption coefficient of 9 × 10 4 L mol −1 cm −1 in solution, which is almost double that of 7T (5.1 × 10 4 L mol −1 cm −1 ) and much larger than those of DCAE7T, DCAO7T, and DCAEH7T in our previous works. [14] The DERHD7T film cast from CHCl 3 shows a broad absorption from 450 to 750 nm and an absorption maximum at 618 nm, which is red-shifted by 110 nm in comparison with that in solution, along with a shoulder peak at 700 nm. This indicates a strong π-π packing between the molecular backbones.…”
mentioning
confidence: 98%